Effectiveness of Lyon Method In Treating Adolescent Idiopathic Scoliosis: A Scoping Review - Zuhaimi, Ummu Hananie; Mohamed Sideek, Mohamed Arshad; Harun Ismail, Ahmad Fahmi (International Journal of Allied Health Sciences, 2024)
Background: Adolescent idiopathic scoliosis (AIS), a three-dimensional spinal deformity occurring in adolescents, can lead to physical limitations and reduced quality of life if untreated. Managing AIS with conservative interventions is often preferable to surgical options, particularly for mild to moderate curves. The Lyon Method, which incorporates structured corrective exercises with bracing, has gained attention for its potential to stabilize and even reduce spinal curvature. Despite its increasing use, the effectiveness of the Lyon Method remains insufficiently documented. This scoping review aims to map and evaluate the current evidence on the Lyon Method’s efficacy in AIS management, identify key outcomes reported in existing studies, and reveal research gaps that require further exploration. Method: This scoping review was conducted following the framework developed by Arksey and O’Malley. A comprehensive literature search was performed in PubMed, Embase, CINAHL, Scopus, and Cochrane Library databases, encompassing studies published up to [insert date]. Studies were eligible if they reported empirical outcomes on the Lyon Method in adolescents with AIS, defined as those aged 10–18 years. Only studies published in English and involving human subjects were considered. Data were extracted and synthesized narratively to account for the diversity of study designs and outcome measures reported. The quality of included studies was assessed using [specify tool if applicable]. Result: The results of this scoping review reveal a range of positive clinical outcomes associated with the Lyon Method for AIS management. Reported benefits include significant improvements in spinal curvature, enhanced muscular strength and endurance, and high levels of patient satisfaction. Additionally, some studies reported improvements in respiratory function and postural balance. However, there is substantial variation in study design, quality, and outcome measures across the reviewed studies, with only a limited number of high-quality randomized controlled trials available. This variation restricts the ability to generalize findings and draw firm conclusions on the overall efficacy of the Lyon Method. Conclusion: Preliminary evidence supports the Lyon Method as a potentially effective conservative intervention for AIS, contributing positively to spinal alignment and functional outcomes. However, more rigorous, standardized studies are necessary to establish stronger evidence and enable more consistent clinical recommendations. This review highlights the Lyon Method’s potential in AIS treatment, emphasizing the need for further high-quality research to validate its effectiveness and refine treatment protocols.